A portable AIEgen-based organic fluorescence sensor design and its reusable application in information storage and pH detection. (16th July 2021) - Ding, Ge; Wang, Xinchao; Zhao, Wenhui; Mao, Shen; Wang, Juan; Kang, Shouting; Meng, Jiangping; Liu, Hongpan; Yang, Heshan; Liang, Shuting
Abstract: The real time pH monitoring is crucial for human body health and environmental protection. In this work, a triphenylamine-conjugated TPA-SA (triphenylamine (TPA) and salicylaldehyde (SA)) with ESIPT segment was successfully designed, synthesized and further applied in pH detection bearing larger Stoke shift. Optical properties indicated that the sensor TPA-SA displayed obvious AIE (aggregation induced emission) phenomenon in DMSO/H2 O (1/1, v/v) mixed solution, nano-scaled granular-like aggregates of TPA-SA could be obtained through scanning electron microscope images (SEM) and dynamic light scattering (DLS). It was worth mentioning that TPA-SA showed excellent fluorescence reaction to changes in pH, and p K a was calculated to be 4.75. In addition, due to its special optical properties, the further practical application of sensor TPA-SA was successfully conducted in pH sensing strips, information storage and the fluorescence cell imaging in HeLa cells, which may be commercially used in near further. Graphical abstract: Image 1 Highlights: Synthesis of pH sensitive AIE chemo-sensor: TPA-SA. TPA-SA presented the recyclable detecting ability for pH with high sensitivity and fast response time. TPA-SA could be fabricated as portable pH test strip to achieve fast detection with pH range from 2.0 to 7.4. The probe was successfully applied as recovered and reused information storage materials.